An oomycete effector subverts host vesicle trafficking to channel starvation-induced autophagy to the pathogen interface - Pandey, Pooja (2021)
Eukaryotic cells deploy autophagy to eliminate invading microbes. In turn, pathogens have evolved effector proteins to counteract antimicrobial autophagy. How adapted pathogens co-opt autophagy for their own benefit is poorly understood. The Irish famine pathogen Phytophthora infestans secretes the effector protein PexRD54 that selectively activates an unknown plant autophagy pathway that antagonizes antimicrobial autophagy at the pathogen interface. Here, we show that PexRD54 induces autophagosome formation by bridging vesicles decorated by the small GTPase Rab8a with autophagic compartments labeled by the core autophagy protein ATG8CL. Rab8a is required for pathogen-triggered and starvation-induced but not antimicrobial autophagy, revealing specific trafficking pathways underpin selective autophagy. By subverting Rab8a-mediated vesicle trafficking, PexRD54 utilizes lipid droplets to facilitate biogenesis of autophagosomes diverted to pathogen feeding sites. Altogether, we show that PexRD54 mimics starvation-induced autophagy to subvert endomembrane trafficking at the host-pathogen interface, revealing how effectors bridge distinct host compartments to expedite colonization.